De novo Synthesis of SAA1 in the Placenta Participates in Parturition - Gan, Xiao-Wen; Wang, Wang-Sheng; Lu, Jiang-Wen; Ling, Li-Jun; Zhou, Qiong; Zhang, Hui-Juan; Ying, Hao; Sun, Kang (Frontiers in Immunology, 2020)
Serum amyloid A1 (SAA1) is an acute phase protein produced mainly by the liver to participate in immunomodulation in both sterile and non-sterile inflammation. However, non-hepatic tissues can also synthesize SAA1. It remains to be determined whether SAA1 synthesized locally in the placenta participates in parturition via eliciting inflammatory reactions. In this study, we investigated this issue by using human placenta and a mouse model. We found that SAA1 mRNA and protein expression in human placental villous trophoblasts, which was increased upon syncytialization and lipopolysaccharides (LPS) treatment. Moreover, significant increases in SAA1 abundance were observed in the placental tissue or in the maternal blood in spontaneous deliveries without infection at term and in preterm birth with histological chorioamnionitis. SAA1 treatment significantly increased parturition-pertinent inflammatory gene expression including IL-1β, IL-8, TNF-α and COX-2 along with increased PGF2α production in syncytiotrophoblasts. Mouse study showed that SAA1 was present in the placental junctional zone and yolk sac membrane, which was increased following intraperitoneal administration of LPS. The induction of parturition by SAA1 was affirmed by intraperitoneal injection of SAA1 in the mouse. Conclusively, SAA1 can be synthesized in the human placenta, which is increased upon trophoblast syncytialization. Parturition is accompanied with increased SAA1 abundance in the placenta. SAA1 may participate in parturition in the presence and absence of infection by inducing the expression of inflammatory genes in the placenta.